SINEMA RELIGI DALAM PUSARAN INDUSTRI MEDIA - Ropingi El Ishaq (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2011)
Normatively, media functions as a means of conveying information, education, andentertainment as well as controlling and relating the society. On the basis of its function,media has a chance to build a direct communication with the society so that it has a strategicposition that may give benefits not only to the social aspect, but also to economic and politicalaspects.One way to develop communication with the public is through soap opera program.This TV program is chosen since it can highly attract public interest. In the point of view ofmedia industry, public or audience are considered as customers who have to be served by theproducer. The more the customers are satisfied, the more the producer gets benefit. One themeof soap operas that can highly attract public interest is religion-related theme.It reflects the normative society understanding of religion. As a result, the religiousmessage contained in the soap operas is very formal. Moreover, since it can highly attractpublic attention, it can be utilized by media industry to get as much profit as they can and itdoes not function to give education and wholesome entertainment.